GE_GERICHTE C/20928/2007 vom 16. Dezember 2016 - GE Cour de justice (2016)
BAIL À FERME AGRICOLE ; PROLONGATION DU BAIL À FERME ; FARDEAU DE LA PREUVE ; SUSPENSION DE LA PROCÉDURE | LBFA.27; CPC.126.1; CC.8;